Służba wojskowa jako źródło sytuacji trudnych w rodzinach żołnierzy (skutki wtórnej traumatyzacji, style wychowania) - Krzemińska-Cieśla, Maria (Chowanna, 2022)
In many scientific studies, the soldier is treated as a socially isolated person; the researchers’ interest is mainly focused on the psychophysical health of representatives of this social group. The article, based on a literature review, analyses the emotional, health and social costs incurred by other members of military families both during and after the soldier’s operations abroad. The article looks at the functioning of military families. Sources of difficult situations that may arise in soldiers’ families are listed, and parental attitudes characteristic of such families are discussed.